DISCOURSE ON OPTIMIZING THE CULTURAL HERITAGE OF BUNG KARNO SCHOOLS IN MOJOKERTO CITY FOR SOCIAL AND ECONOMIC WELFARE - Rio Febriannur Rachman (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2020)
In 2019, the City Government of Mojokerto declared two schools, SDN Purwotengah and SMPN 2 Kota Mojokerto as cultural heritage. Soekarno also known as Bung Karno, one of the founding fathers of this country, Indonesia, studied there, on 1908 until 1916. This study discusses how the discourse on optimizing the cultural heritage of Bung Karno's two schools as historical tourism objects, from the perspective of social and economic welfare of the community. The theory used in this study is public policy, popularized by Thomas Dye and James E. Anderson. This study uses a qualitative method with the discourse analysis approach of Norman Fairclough. The discourse analyzed anything was conveyed by the Mayor of Mojokerto Ika Puspitasari and the Head of the Education Office Amin Wachid in the Srawung program, which aired from 16.00 to 17.00, 18 August 2020, on TVRI East Java. The result of this study indicates, the City Government of Mojokerto is serious, regarding make historical tourism objects in the cultural heritage buildings of the Bung Karno Schools. The City Government of Mojokerto considers, it will further foster a sense of community nationalism, provide authentic historical insights, as well as emerge a populist economy.keywords: Cultural Heritage, Discourse, Public Policy, Social and Economic Welfare